A novel policy to tackle life span reassessment of existing bulk and thin-film photovoltaic materials. (23rd July 2021) - Sheoran, Manisha; Kumar, Pancham; Sharma, Susheela
With the growing planetary demands of clean energy, solar photovoltaic system electricity generation has become mandatory in today's world. At the same time, when we look towards photovoltaic waste volume in India, it is estimated to burst forth to 200, 000 by 2030 and around 1.8 million tons by 2050. Therefore, there is a dire need to scale up the PV recycle method from lab to full-fledged industry. Most of the developed countries such as China, UK, Japan, etc. have ensued their PV scarp management policies but in context to Indian prospective, it is yet to be established. The paper focuses on the effective remedy of environmental and socio-economic impact arising during the life span fulfilment of c-Si, CdTe, CdS and CIS. Over here, a sustainable novel policy framework is put forward to potentially tackle the above-mentioned problem which is still to be adopted by the Indian Government for further implementation.